Psychological burden among women with polycystic ovarian syndrome in Oman: a case–control study - Sulaiman MA; Al-Farsi YM; Al-Khaduri MM; Waly MI; Saleh J; Al-Adawi S (Dove Medical Press, 2017)
Maha AH Sulaiman,1 Yahya M Al-Farsi,1 Maha M Al-Khaduri,2 Mostafa I Waly,3 Jumana Saleh,4 Samir Al-Adawi5 1Department of Family Medicine and Public Health, 2Department of Obstetrics and Gynecology, College of Medicine and Health Sciences, 3Department of Nutrition and Food Sciences, College of Agricultural and Marine Sciences, 4Department of Biochemistry, 5Department of Behavioral Medicine, College of Medicine and Health Sciences, Sultan Qaboos University, Al-Khoudh, Muscat, Sultanate of Oman Purpose: Previous studies in Euro-American populations have shown that women with polycystic ovarian syndrome (PCOS) have increased levels of “psychological burden”. While PCOS has been reported in Arab countries such as Oman, there is a dearth of studies of the occurrence of psychological burden among PCOS women in the Arab region. This study aimed to compare sociodemographic and clinical characteristics of PCOS women diagnosed with non-PCOS women and prevalence of severity of depression, anxiety and stress and to explore the association between PCOS and indices of psychological disturbances after adjusting for potential confounding factors.Patients and methods: This hospital-based case–control study was conducted among women aged 16–49 years. The study included 52 women diagnosed with PCOS (as per Rotterdam 2003 criteria) and 60 control who were PCOS-free. The presence of psychological burden – depression, anxiety and stress – was quantified using Depression, Anxiety and Stress Scale-21 (DASS-21).Results: The crude odds ratios (ORs) generated by logistic regression models indicated an increased risk of depression, anxiety and stress among women with PCOS compared to controls. The adjusted OR also indicated an increased risk of depression (OR =1.10; 95% confidence interval [CI] 0.50, 2.43), anxiety (OR =1.09; 95% CI 0.47, 2.52) and stress (OR =1.45; 95% CI 0.68, 3.12), However, no statistical differences were observed along the three psychological distresses (p>0.05) between the two study groups.Conclusion: The study indicates that the presence of PCOS is associated with an increased risk of psychological burden. If this study will withstand further scrutiny, meeting psychological needs of such population would need to be contemplated. Keywords: PCOS, depression, anxiety, stress, Oman, case–control